The Impact of Financial Technology, Islamic Financial Literacy, and Behavioral Biases on Investment Decisions in the Sharia Capital Market - Rahmi Fauzah, Dhiya; Amaliyah, Kharisma A (International Journal of Islamic Finance, 2023)
The development of the number of investors in the Indonesian Capital Market continues to increase year after year, including investors in the Sharia Capital Market. Indeed, this cannot be separated from the investment decisions that the investors have made. This study aims to analyze the effect of Financial Technology, Islamic Financial Literacy, Overconfidence Bias, and Herding Bias on investment decisions in the Sharia Capital Market. This paper presents a new research treatise or a renewable gap in the scope of Islamic Finance because it is more specifically related to investment decisions in Sharia Capital Market and Muslim Investor samples which are different from previous studies. As a quantitative research, this study used Partial Least Square-Structural Equation Model (PLS-SEM) analysis with the help of SmartPLS software and used data from 190 respondents that was collected through the questionnaire method. The result found that Financial Technology, Islamic Financial Literacy, and Overconfidence Bias have positive and significant impacts on Investment Decisions in the Sharia Capital Market, while Herding Bias known to have no positive and significant effects on investment decisions in the Sharia Capital Market. The paper provides empirical evidence that can contribute to the development of knowledge and insight in the field of Economics and Business Islam through Sharia Financial Management research related to Investment Decisions in the Sharia Capital Market, and it is practically helpful for academics, investors, and researchers.